The role of anxiety and adaptation to illness in the intensity of postchemotherapy nausea in cancer patients. - Pallarés, Cinta; Alonso, Carmen; Blasco, Tomás; López López, Juan José (The Spanish Journal of Psychology, 2000)
Sin resumen